A study on the derivation of parametric cutting force equations in drilling of GFRP composites - Okutan, Eda (Strojniški vestnik, 2013)
The aim of the present work is to derive machine force equations in the drilling of 0°/+45°/90°/45° oriented glass fiber reinforced polymeric matrix composites (GFRP). The novelty is in the use of the Shaw and Oxford model, which was initially developed for metals, for GFRP composites. The machining was performed on the GFRP samples using 118° point angle drills under dry conditions. During machining, drill torques and thrust force fluctuations were recorded using a dynamometeramplifiercomputer combination with different feed rates and drill diameters. The collected data were then analysed using mathematical models to investigate the empirical relationships between the essential parameters. The cutting forces in the drilling of GFRP materials were calculated using empirical equations and the results were compared with the measured data to verify the accuracy of the derived equations for the drilling of glass fiber reinforced polymer matrix materials. Moreover, the whole surface morphology of the drilled GFRP samples was examined by optical microscope and scanning electron microscope (SEM).
Keywords: drill torque; empirical equation; empirična enačba; GFRP; glass fiber reinforced polymer; machinability; morfologija površine; obdelovalnost; potisna sila; steklena vlakna; surface morphology; thrust force; vrtalni navor